Uniaxial compression mechanical property and fracture behavior of hybrid inorganic short mineral fibers reinforced cement-based material. (November 2019) - Yang, Yuanyi; Zhou, Qi; Li, Xingkui; Lum, Galen Chit; Deng, Yi
Abstract: The mechanical strength, uniaxial compression, three points flexure toughness and microstructure of a novel fiber hybridization of brucite and basalt short fibers reiforced cement-based material were carried out in this manuscript. The highest improvement in compressive strength, tensile strength and flexural strength of the samples was 68.7%, 142.6%, and 88.8%, respectively. Additionally, the constitutive model of the hybrid mineral fibers sample was established. Through the fracture toughness investigation, the employment of fiber hybridization enhanced the fracture toughness K Ι c S and K Ι c Q of cement-based material by 127% and 184% times, respectively. The incorporation of hybrid mineral short fibers increased the linear elastic fracture toughness energy G F by 364% times and elastic-plastic fracture toughness energy J C by 181% times. Due to different elasticity modulus and fiber dimensions, the mineral fibers hybridization not only dramatically boosted the fracture energy, the strength, and deformability, but also effectively restricted the initiation and propagation of cracks in different dimensions.